O processo criativo em Segredo de Estado, de Antonieta Dias de Moraes : marcas do militarismo e representações sociais - Menezes, Ivanildes Regina de (2015)
This research proposes investigate the creative process of Secret of State (1998), by Antonieta Dias de Moraes (1915-1999) and aims to show traces of Brazilian military context in order to capture the ways of living and thinking of the society immersed in the violent period of dictatorship in Brazil. The memory of this time must be constantly remembered due to the enhancement of the democracy which we live now, even though dark reflexes of that regime persist in our society nowadays, more than 30 years later. Dominated by shadows in diverse sectors, Brazilian society have found a way of resistance in the arts, which produced artworks of different kinds over distinct strategies, either inside the country and, many times, out of it. In this case, those works were produced by political deportees who left their country by force or by choice, in order to continue their creations during the dictatorial regime. It was during the military dictatorship period, especially in the most violent moment of it – Médici’s government (1968-1974) –that the writer Antonieta Dias de Moraes represented social problems in the majority of her books, published firstly abroad and only afterwards in Brazil. Considered a classic of children’s literature, Secret of State tells about the participation of Tonico’s gang in São Paulo State Revolt of 1924, which began in the same state capital, led by mid-rank military officers and by Public Force. Their claim was to justice and the end of corruption. In the book,Tonico’s gang helped the army with bravery and perspicacity, providing a valuable contribution to the Revolt. Conceived during the dictatorial repression, this book describes a scenario where children pursued fairer living conditions, in which we may read, between the lines, the possibility of identification of the historical context (1924) and the period of repression and resistance lived by the nation (60’s and 70’s decades). Based on heterogeneous objects of research, composed by book manuscripts, drafts, copies, fragments, letters, newspaper clippings and illustrations, this research, thus, proposes to investigate the creative process of Secret of State. The methodology covers the initial identification of the objects, the making of a genetic critic dossier of the book’s composition and the analysis of the records left by the author in the different pieces that integrate her personal archive located in the historic farm Santa Eudóxia (São Carlos, São Paulo State). So, this work is an effort to create the minimum requirements for the comprehension of the book’s genesis and its representation of social reality. Added to the genetic analysis, some reflections are supplied by Bakhtin’s theory of language, which tells about the different voices present in a textual object. These voices are permeated by different styles and intentions, marked by their emerge in a certain social, political and economic context. Finally, this work concludes that Secret of State, written by Antonieta Dias de Moraes during the military dictatorship period, is a book that enriches the list of literary texts in which are recognizable the popular denouncement and discontentment, in addition to other marks that every authoritarian regime leaves in society, which are thematized by those who oppose the imposed order by the means of artistic language.